Pengaruh Transformasi Sistem E-Learning Terhadap Minat Belajar Siswa Sekolah Menengah Kejuruan (Smk) Wikrama Di Kota Bogor - Iskandar Abubakar; Gina .; Cahyono T Wibowo (Institut Pertanian Bogor, 2014)
ABSTRACTE-Learning is a learning process electronically and remotely can be done without face to face interactions informally with a simpler, for example by means of mailing lists, e-newsletters or personal websites, organizations and companies that want to socialize services, programs, knowledge or particular skills in societies.This study was to determine the e-learning teaching system, determine the effect of the transformation of e-learning system to students, and students' interest in learning to know the e-learning system. This research using quantitative methods with a sample of 60 students. Data collected through questionnaires. Analysis of the data using product moment The results showed that the learning system of e-learning considered less effective as face-to-face communication is still used only used to provide enrichment and test materials. Effect of the transformation of the system of e-learning relatively new, so it is still weak and the students themselves have not understood in depth. Student interest to study e-learning systems is still low because of e-learning is still in the introduction stage. Effect of the transformation of e-learning system on student interest is very weak because it is still using the system dependence learn face to face with the teacher.Key Words: E-Learning, Communication, Student